2014
DOI: 10.1016/j.ccr.2014.05.029
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo Transducer YAP1 Transforms Activated Satellite Cells and Is a Potent Effector of Embryonal Rhabdomyosarcoma Formation

Abstract: The role of the Hippo pathway effector YAP1 in soft tissue sarcomas is poorly defined. Here we report that YAP1 activity is elevated in human embryonal rhabdomyosarcoma (ERMS). In mice, sustained YAP1 hyperactivity in activated, but not quiescent, satellite cells induces ERMS with high penetrance and short latency. Via its transcriptional program with TEAD1, YAP1 directly regulates several major hallmarks of ERMS. YAP1-TEAD1 upregulate pro-proliferative and oncogenic genes and maintain the ERMS differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
195
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(216 citation statements)
references
References 52 publications
20
195
1
Order By: Relevance
“…Both genetic and pharmacologic inhibition of YAP/TEAD and FOXM1 result in sarcoma cell proliferation defects, suggesting that these targets represent promising therapeutic interventions for mesenchymal tumors. Very recent studies have shown that YAP overexpression and function plays a role in the pediatric malignancies alveolar embryonal rhabdomyosarcoma (aRMS) and embryonal rhabdomyosarcoma (eRMS) (23,24). Together with these findings, we conclude that the Hippo pathway is potentially important in multiple sarcoma subtypes.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Both genetic and pharmacologic inhibition of YAP/TEAD and FOXM1 result in sarcoma cell proliferation defects, suggesting that these targets represent promising therapeutic interventions for mesenchymal tumors. Very recent studies have shown that YAP overexpression and function plays a role in the pediatric malignancies alveolar embryonal rhabdomyosarcoma (aRMS) and embryonal rhabdomyosarcoma (eRMS) (23,24). Together with these findings, we conclude that the Hippo pathway is potentially important in multiple sarcoma subtypes.…”
supporting
confidence: 51%
“…4F). We were particularly intrigued by our findings in the rhabdomyosarcoma cell line, because recent reports have implicated Hippo pathway perturbations here (23,24). YAP expression has been shown to be elevated in these tumors compared with normal tissue and to promote tumor growth in this context.…”
Section: Injection We Minimizedmentioning
confidence: 89%
“…Although mutations in the Hippo pathway are rare, mutation or deletion of Lats2 is significant in malignant mesothelioma (16). Furthermore, the oncoprotein YAP has been implicated in promoting the formation of several types of tumors, such as liver and skin tumors and rhabdomyosarcoma (17)(18)(19)(20)(21). As expected, overexpression or hyperactivation (nuclear localization) of YAP is frequently detected in several human malignancies, including liver, ovarian, breast, lung, and pancreatic cancer (18)(19)(20)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 93%
“…Because the very character of each experiment results in tumorigenesis or no tumorigenesis, any untested variable may be the key between the 2 potential results. For example, elegant work by others has recently demonstrated that the sarcomagenesis-originating potential of satellite cells in particular depends on their activation in response to injury (37,38). Our experiments did not address the application of this principle to synovial sarcomagenesis, but future work should.…”
Section: Discussionmentioning
confidence: 97%